The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1149/1.2719597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxide on Trench Edge Defect Formation in Ion-Implanted Silicon

Abstract: An investigation of the defects that form near oxide-filled trenches during solid-phase epitaxy of amorphous silicon produced by ion implantation was conducted. It was observed that defects form near the trench edge after recrystallization. Defect formation resulted from pinning of the initial amorphous/crystalline interface at the trench edge and regrowth proceeded until triangular amorphous regions bound by the surface, trench, and ͑111͒ plane were formed. Regrowth of the triangular regions then proceeded al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 15 publications
(15 reference statements)
2
20
0
Order By: Relevance
“…In fact, it was previously shown that the SPEG process in similar structures on (001) wafers results in faceting of the growth interface along the same {111} plane with the growth interface pinned at the initial point of contact with the SiO x -filled trench; this results in a triangular region of α-Si bound by the SiO x -filled trench, the wafer surface, and the {111} plane (Burbure et al, 2007). It should also be noted that similar faceting was observed for SPEG in the vicinity of SiO x -filled trenches for wafer orientations other than (001) (Saenger et al, 2007a).…”
Section: Growth Interface Termination On One Sidementioning
confidence: 99%
“…In fact, it was previously shown that the SPEG process in similar structures on (001) wafers results in faceting of the growth interface along the same {111} plane with the growth interface pinned at the initial point of contact with the SiO x -filled trench; this results in a triangular region of α-Si bound by the SiO x -filled trench, the wafer surface, and the {111} plane (Burbure et al, 2007). It should also be noted that similar faceting was observed for SPEG in the vicinity of SiO x -filled trenches for wafer orientations other than (001) (Saenger et al, 2007a).…”
Section: Growth Interface Termination On One Sidementioning
confidence: 99%
“…Conventional (111)-oriented solid-phase epitaxial growth [15][16][17][18] has been achieved by utilizing latticematched epitaxy during thin-film growth as long as the lattice misfit is less than 8%. On the other hand, Narayan et.al [19,20] has showed that a large lattice misfit relative to the substrate can still grow epitaxial layers, which is called 'domain matching epitaxy (DME)', where integral multiples of the lattice constants make a good lattice matching between the substrate and the over-grown layer [21].…”
Section: Introductionmentioning
confidence: 99%
“…After that, a 150 nm thick Si layer was deposited by physical vapor deposition (PVD) at 450°C. Then the sample is further annealed at 950°C [18] in an atmospheric electric furnace to crystallize the Si film. The temperature was same as a previous paper which reports (111) epitaxial growth of Si on Si seed substrate [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of extended defects near the ion implantation mask edges after dopant annealing has been reported. [10][11][12] The types and spatial distribution of extended defects depends on the length scales of the ion implantation edges, and the ion implantation doses. In particular, for silicon amorphized with high dose (1x 10 15 cm −2 ∼ 1x 10 16 cm −2 ) self-implantation, dislocation loops were frequently observed after solid phase epitaxial regrowth (SPER).…”
mentioning
confidence: 99%